2016
DOI: 10.1111/1365-2656.12600
|View full text |Cite
|
Sign up to set email alerts
|

Admixture is a driver rather than a passenger in experimental invasions

Abstract: In this issue of Journal of Animal Ecology, Wagner et al. (2017) demonstrate that genetic diversity can alter the course of spread of biological invasions. They employ Callosobruchus seed beetles in a clever array of linked habitat patches to compare experimental invasions using individuals from single population sources or from mixes of two, four or six population sources. By taking a model-selection approach, they find that any amount of mixture propels growth rates and spread of introduced populations. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…In this issue, we start the year with a ‘ How to …’ by Matthew Wolak and Jane Reid on ‘How to include genetic groups in quantitative genetic animal models and accounting for genetic differences among unknown parents in microevolutionary studies’ (Wolak & Reid ). The In Focus for this issue is by Ruth Hufbauer (), who discusses the paper by Wagner et al . () that looks at how the genetic mixture of multiple source populations can catapult the spread of biological invasions.…”
Section: In This Volumementioning
confidence: 99%
“…In this issue, we start the year with a ‘ How to …’ by Matthew Wolak and Jane Reid on ‘How to include genetic groups in quantitative genetic animal models and accounting for genetic differences among unknown parents in microevolutionary studies’ (Wolak & Reid ). The In Focus for this issue is by Ruth Hufbauer (), who discusses the paper by Wagner et al . () that looks at how the genetic mixture of multiple source populations can catapult the spread of biological invasions.…”
Section: In This Volumementioning
confidence: 99%
“…Several studies have reported that genetic admixtures facilitate invasion through the short‐term mechanism of hybrid vigor (Facon, Jarne, Pointier, & David, ; Li, Stift, & van Kleunen, and see below). This mechanism, also termed heterosis, arises through the dominant effect that one parental allele masks the other, and/or through over‐dominant allelic interactions that heterozygotes outperform any homozygous genotypes (Hufbauer, ; Rius & Darling, ). The heterotic effect not only facilitates the colonization of exotic plants (Hahn & Rieseberg, ; Keller & Taylor, ; van Kleunen, Röckle, & Stift, ) and animals (Drake, ; Facon et al, ) but also serves as the driving force for invasive range expansion (Hufbauer, ; Wagner, Ochocki, Crawford, Compagnoni, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism, also termed heterosis, arises through the dominant effect that one parental allele masks the other, and/or through over‐dominant allelic interactions that heterozygotes outperform any homozygous genotypes (Hufbauer, ; Rius & Darling, ). The heterotic effect not only facilitates the colonization of exotic plants (Hahn & Rieseberg, ; Keller & Taylor, ; van Kleunen, Röckle, & Stift, ) and animals (Drake, ; Facon et al, ) but also serves as the driving force for invasive range expansion (Hufbauer, ; Wagner, Ochocki, Crawford, Compagnoni, & Miller, ). However, this mechanism appears to be short‐lived, sometimes existing only in one generation (Drake, ), and decays rapidly over generations (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While many factors will shape the success of species introductions and their ecological interactions with recipient environments (Sakai et al, ), there is increasing evidence that genetic factors can play a role in this process (Baker & Stebbins, ; Colautti & Barrett, ; Cox, ; Ellstrand & Schierenbeck, ; Lee, ; Mesgaran et al, ; Rius & Darling, ; Whitney & Gering, ). Understanding when, where, and how genetic changes influence the outcomes of colonization is likely to be crucial to resolving broader questions about when species introductions will lead to establishment and invasive spread (Bock et al, ; Colautti & Lau, ; Dlugosch, Anderson, Braasch, Cang, & Gillette, ; Forsman, ; Hufbauer, ; Lee & Gelembiuk, ; Ochocki & Miller, ; Rius & Darling, ; Szűcs, Melbourne, Tuff, & Hufbauer, ; Szűcs, Melbourne, Tuff, Weiss‐Lehman, & Hufbauer, ; Weiss‐Lehman, Hufbauer, & Melbourne, ; Williams, Kendall, & Levine, ).…”
Section: Introductionmentioning
confidence: 99%
“…These same mechanisms are known to have contributed directly to non‐native species establishment and the rise of particularly invasive novel genotypes in cases involving hybridization between species, and the potential for similar benefits of admixture within species appears widespread (Drake, ; Ellstrand & Schierenbeck, ; Hovick & Whitney, ). Consequently, there is intensifying interest in the potential for genetic admixture to provide a general mechanism by which many non‐native species are able to establish and develop into invaders (Bock et al, ; Dlugosch, Anderson, et al, ; Frankham, ; Hufbauer, ; Molofsky, Keller, Lavergne, Kaproth, & Eppinga, ; Rius & Darling, ; Verhoeven, Macel, Wolfe, & Biere, ).…”
Section: Introductionmentioning
confidence: 99%